Entrepreneurial roles, creativity and play - Antila, Anu (My University, 2019)
Previous research has defined diverse entrepreneurial identity roles. Although the division between these roles is clear, the impact of these roles on entrepreneurial ventures and the daily actions of entrepreneurs is yet rather ambiguous. Further, creativity and play are essential components of entrepreneurship. This derives from the significant influence creativity and play have on the emergence of innovation which is essential in entrepreneurship. However, since creativity and playfulness are not well-acknowledged in an organizational context nor in entrepreneurship as such, this study aims to increase the knowledge of creativity and play as a mediator to increase entrepreneurial emergence. The present Master’s thesis thus focuses on the relationship between entrepreneurial identity roles, creativity and play. The purpose of the study is to find out which types of creativity and play different entrepreneurial identity roles may invoke. The study was conducted through an exploratory research utilizing qualitative research methodologies to analyze the findings of semi-structured interviews. The interviews were conducted to gain the insights of five entrepreneurs and their subjective approach to different types of creativity and play which they utilize in their daily entrepreneurial endeavors. In order to analyze the impact of entrepreneurial identity role on the reported types of creativity and play, the interviewees were asked which one of the roles (1) inventor identity, (2) founder identity, and (3) developer identity would best describe them. The findings of the study suggest that there are some connections between the types of creativity and play invoked by particular entrepreneurial identity roles. The study was able to define the source of motivation related to each entrepreneurial identity role. Moreover, the study distinguished degrees of proactive and responsive creativity between the roles. In terms of play, the study reconciled the purpose of play which different roles are likely to utilize. Further, the study determined different types of play and was able to define which entrepreneurial identity role is likely to exploit certain types of play. However, since entrepreneurs may relate to several entrepreneurial identity roles at the same time, it is challenging to determine specific types of creativity and play invoked by a certain entrepreneurial identity role. Moreover, since creativity and play, as concepts, are rather scarcely utilized in the daily endeavors of entrepreneurs, more research should be conducted to increase the knowledge of the influences of these on entrepreneurial performance. This study contributes to the research on entrepreneurial identity roles with the perspective of creativity and play. Moreover, the study increases the practical insights of the variety of entrepreneurial identity roles.
Keywords: entrepreneurship; entrepreneurial roles; creativity; play; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business